A problem with shift for a mixed-type model equation of the second kind in an unbounded domain - Zunnunov, R.T.; Ergashev, A.A. (Bulletin of the Karaganda University. Mathematics Series, 2022)
This article studies a problem with shift in the characteristics of different families in an unbounded domain for a mixed-type model equation of the second kind. The elliptic part of this problem is the vertical halfstrip; the hyperbolic part is the characteristic triangle bounded by the characteristics of the equation. Using the extremum principle we prove the uniqueness of the solution. With the integral equations method we prove the existence of the solution.